Changes in leukocyte counts, lymphocyte subpopulations and the mRNA expression of selected cytokines in the peripheral blood of dogs with atopic dermatitis - Z. Hoskova; M. Svoboda; D. Satinska; J. Matiasovic; L. Leva; M. Toman (Veterinární Medicína, 2015)
Canine atopic dermatitis (CAD) is a chronic allergic disease characterised by genetic predisposition. The exact pathogenesis of the disease is still not fully understood. Blood parameters, lymphocyte subpopulations, cytokines and other molecules involved in pro- and anti-inflammatory activities, and Th1/Th2 polarisation in peripheral blood were assessed in clinically healthy dogs and dogs with AD by haematological examination, flow cytometry and qRT-PCR. The group of diseased dogs was further divided into subgroups according to the severity of clinical signs expressed as CADESI-03 (canine atopic dermatitis extent and severity index) values. The group of dogs with CAD showed mild neutrophilia without general leucocytosis, reduced numbers of B-lymphocytes (P < 0.05), increased relative numbers of T-lymphocytes (P < 0.01) decreased absolute numbers of double-positive lymphocytes (P < 0.001) and NK cells (P < 0.05) as compared with healthy controls. The expression levels of IL-10 mRNA were significantly higher (P < 0.05) in the group with CAD. Correlation with CADESI-03 was observed in expression levels of CCL3 (P < 0.05), CCL5 (P < 0.05) and SOCS-3 mRNAs (P < 0.05). In conclusion, the disease stage investigated in the present study is characterised by a chronic inflammatory response.